Penggunaan Model Pembelajaran Kooperatif Tipe Make A Match Untuk Meningkatkan Penguasaan Kosakata Bahasa Arab Siswa Kelas VII A MTs Jabal An-Nur Al-Islami - Sastrawan, Doni (An Naba, 2022)
The teacher is central to the learning process because he must have a special strategy, so that students can understand and understand the subject matter presented. Based on the observations made, the lack of mastery of student vocabulary, as well as students from public elementary school backgrounds, makes students less active in the learning process which has an impact on mastering their Arabic vocabulary. This class action research aims to: 1) To determine the process of implementing teaching and learning activities using a Make a Match type cooperative learning model for class VII A MTs Jabal An-Nur Al-Islami Bandar Lampung students, 2) To improve the ability to master Arabic for students of class VII A MTs Jabal An-Nur Al-Islami Bandar Lampung. This study was conducted in three cycles, the first cycle with two meetings and one meeting for the test, with the results of the average value in cycle I of 75.52. In the second cycle with two meetings and one test, with an average score of 85.21, it was more increased than the average value of the first cycle test of 75.52. In the third cycle with two meetings and one test, with an average score of 90.78, it was more increased than the average value of the cycle II test of 85.21. Based on the existing problems and the objectives of the researchers above that students' ability to master Arabic vocabulary increases in each cycle, this can be seen from the results of the average score of the test or evaluation in each cycle so that the cooperative learning model can be an alternative in student Arabic learning.